Affinity Replica Selection in Distributed Systems - Wan Awang, Dr. Wan Suryani; Mohd Rose, Prof. Madya Dr. Ahmad Nazari; Mohamad, Prof. Madya Dr. Zarina (Springer, 2019)
Replication is one of the key techniques used in distributed systems to improve high data availability, data access performance and data reliability. To optimize the maximum benefits from file replication, a system that includes replicas. A replica selection strategy determines the available replicas and chooses the most access files. In most of these access frequency based solutions or popularity of files are assuming that files are independent of each other. In contrast, distributed systems such as per-to-peer file sharing and mobile database, files may be dependent or correlated to one another. Thus, this paper focused on the combination of popularity and affinity files as the most important parameters in selecting replicas in distributed environment. Herein, a replica selection is proposed focusing om popular files and affinity files. The idea is to improve data availability in distributed data replica selection strategy. A P2P simulator, PerrSim, is used to evaluate the performance of the dynamic replica selection strategy.